Conservation Challenges of Two Monitor Lizards [Varanus bengalensis (Daudin, 1802) and Varanus salvator (Laurenti, 1768)] in Jorhat, Assam, India - Borthakur, Atrayee; Gohain, Shekhar Jyoti Borpatra (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Varanus bengalensis (Daudin, 1802) and Varanus salvator (Laurenti, 1768), both protected under Schedule I of the Wild Life (Protection) Act, 1972, continue to be hunted across India due to culinary preferences and ethno-medicinal beliefs. In addition, human-wildlife conflict often results in retaliatory killings. This study investigates the hunting practices involving these monitor lizard species in the Sarucharai region of Jorhat, Assam. Structured surveys were conducted with 200 individuals across 50 households. Among the respondents, 52% reported consuming meat from V. bengalensis or V. salvator, with an estimated annual hunting rate of 1–7 individuals. Furthermore, 11% admitted to hunting the reptiles, 19% to preparing their meat, and 46% were familiar with cooking techniques. Notably, 64% of respondents believed the meat could alleviate rheumatic pain, although only 1% reported a clinical diagnosis of rheumatism. Similarly, 41% believed the skin could treat burning lesions, with 6% having used it for the same. While 72% were aware of the legal laws protecting the species, only 30% understood their ecological or conservation significance. Reports of predation on poultry and fish were also considerable, with 46% of households affected. These findings underscore persistent hunting practices and low conservation awareness, emphasizing the urgent need for enhanced law enforcement and community-based conservation outreach.